2000
DOI: 10.1002/(sici)1097-4628(20000509)76:6<913::aid-app18>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ternary copolyamides from aromatic diamine (m-phenylenediamine, diaminodiphenylsulfone), aromatic diamine with carboxyl or sulfonic group (3,5-diaminobenzoic acid, 2,4-diaminobenzenesulfonic acid), and iso- or terephthaloyl chloride

Abstract: ABSTRACT:The copolymerization of iso-or terephthaloyl chloride, m-phenylenediamine or diaminodiphenylsulfone, and 3,5-diaminobenzoic acid or 2,4-diaminobenzene sulfonic acid (or sulfonate) was studied. Copolymers with high reduced viscosity could be obtained by low temperature solution polymerization, but not by interfacial polymerization. The reduced viscosity of the copolyamides obtained was dependent upon the species of the aromatic diamine compounds and the acid acceptors used. Low temperature solution cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 11 publications
0
26
0
1
Order By: Relevance
“…Measurements of water permeability and salt rejection were reported. Recently, Konagaya et al [8] have reported the polymerization of carboxylated or sulfonated copolyamides in order to achieve not only good reverse osmosis performance but also better chlorine resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of water permeability and salt rejection were reported. Recently, Konagaya et al [8] have reported the polymerization of carboxylated or sulfonated copolyamides in order to achieve not only good reverse osmosis performance but also better chlorine resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Miyazaki et al [64] reported that aromatic polyamides containing carboxyl groups (polyamide-COOH) [65] show hydroxyapatite-forming ability in 1.5SBF when they contain CaCl 2 (Figure 11.21). The hydroxyapatite layer was tightly attached to the polymer and was not peeled off by the tape test.…”
Section: Hydroxyapatite Deposition On Synthetic Polymersmentioning
confidence: 99%
“…1, 11 was dissolved in 10 mL of N, N-dimethylacetamide Wako Pure Chemical Ind. together with 0.67 g of CaCl 2 Nacalai Tesque Inc. .…”
Section: Preparation Of Polyamide Filmmentioning
confidence: 99%